The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.24001/ijels.2.5.1
|View full text |Cite
|
Sign up to set email alerts
|

Attitude towards Women in Managerial Positions: A study among Undergraduate Students of the University of Ghana

Abstract: Abstract-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
1
2
0
Order By: Relevance
“…This finding confirms earlier studies which found higher level of assertiveness among males compared to females [10,25]. As explained by Addai et al [26], women are still perceived as sex objects and trophies accorded with little respect in some societies as demonstrated in the media-adverts, musical clips, bill boards and magazines. Moreover, some societies perceive women as the object of men when they get marriage.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This finding confirms earlier studies which found higher level of assertiveness among males compared to females [10,25]. As explained by Addai et al [26], women are still perceived as sex objects and trophies accorded with little respect in some societies as demonstrated in the media-adverts, musical clips, bill boards and magazines. Moreover, some societies perceive women as the object of men when they get marriage.…”
Section: Discussionsupporting
confidence: 90%
“…This has the tendency to make women less assertive. Moreover, as proposed by Addai et al [26], sex difference in assertiveness is also based on traditionally established stereotype. Certain behaviours are said to be male oriented.…”
Section: Discussionmentioning
confidence: 99%
“…However, a large number of studies (e.g. Güney, Gohar, Akıncı, & Akıncı, 2006;Adeyemi-Bello & Tomkiewicz, 1996;Preko, 2012) studies this or related issues have also used a "hybrid" scale combining two or more scales.…”
Section: Measure Of Attitude Towards Women Leadership At the Workplacementioning
confidence: 99%